A Study on Adults’ Perception Towards The Use of Child Restraint System (CRS) in Batu Pahat, Johor - Suwarna Subramaniam; Nursitihazlin Ahmad Termida (Recent Trends in Civil Engineering and Built Environment, 2021)
Child Restraint System (CRS) is a tool to protect children from road collisions. Many children still remain unstrained or improperly restrained. Therefore, it is essential to understand the significance of CRS usage and the perceptions of adults’ in utilizing CRS. Thus, objective 1 for this study is to determine the factors influencing adults’ perception in utilizing CRS. Meanwhile, objective 2 is to investigate the relationship between the use of CRS and the factors influencing adults’ perception in utilizing CRS. A questionnaire in a form of Google Form was developed and distributed to 384 respondents whose age 18 years old and above in Batu Pahat areas via the online platform. The data obtained were analyzed using a statistical package for social science (SPSS) version 26.0. Exploratory Factor Analysis (EFA) method is utilized to achieve objective 1. 3 factors are obtained from EFA namely child safety, perceptions of adults’ on CRS, and barriers of installing CRS. The Chi-square test is used to achieve objective 2. Based on the mean score, the factors that result in the high usage of CRS among adults in Batu Pahat areas are child safety and perceptions of adults’ on CRS. Meanwhile, the factor that results in the low usage of CRS among adults’ in Batu Pahat areas is the barriers in installing CRS. Therefore, the Chi-Square test shows that there is a significant relationship between the use of CRS and the factors influencing adults’ perception of utilizing CRS. Hence, many initiatives can be introduced such as a strict implementation of the CRS law in Malaysia, promotions for child safety seats, and convertible CRS type for children.